The Relationship Between Nutrition and Atherosclerosis - Wei, Taotao; Liu, Junnan; Zhang, Demei; Wang, Xiaomei; Li, Guangling; Ma, Ruchao; Chen, Gang; Lin, Xin; Guo, Xueya (Frontiers in Bioengineering and Biotechnology, 2021)
Atherosclerosis is the basic pathological process of many diseases, such as coronary atherosclerosis and stroke. Nutrients can affect the occurrence and development of atherosclerosis. At present, in nutrition science, the research on atherosclerosis focuses on which nutrients play an important role in its prevention strategy, and what are the possible mechanisms of its action. In the current study, the process of atherosclerosis can be affected by adjusting the proportion of nutrients in the diet. In this review, we pay attention to the effects of phytosterols, omega-3-polyunsaturated fatty acids, polyphenol, vitamin and other nutrients on atherosclerosis, pay attention to their current epidemiological status, current nutritional research results, and prevention or a possible mechanism to reduce the risk of development of atherosclerosis. So that more personalized nutritional approaches may be more effective in terms of nutritional intervention responses to atherosclerosis.